2022
DOI: 10.3389/fnut.2022.966248
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of largemouth bass (Micropterus salmoides) fed trash fish and formula feeds: Growth, flesh quality and metabolomics

Abstract: This study compared the growth, flesh quality and metabolomics of largemouth bass (Micropterus salmoides) fed trash fish and formula feeds. Trash fish (TF), self-made feed (SF) and commercial feed (CF) were prepared with crude protein levels of 172.2 g/kg, 503.5 g/kg and 504.1 g/kg (666.2 g/kg, 547.3 g/kg and 535.1 g/kg based on dry matter), respectively. Then, the three diets were fed to largemouth bass with an initial body weight of 75.0 ± 0.1 g for 12 weeks. SF and CF groups presented significantly lower fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Inosine monophosphate is an endogenous substance related to meat flavor [19]. Research has shown that the pectoral muscles of five local chicken lines in Korea had higher levels of inosine monophosphate than the leg muscles [20].…”
Section: Muscle Meat Quality Characteristicsmentioning
confidence: 99%
“…Inosine monophosphate is an endogenous substance related to meat flavor [19]. Research has shown that the pectoral muscles of five local chicken lines in Korea had higher levels of inosine monophosphate than the leg muscles [20].…”
Section: Muscle Meat Quality Characteristicsmentioning
confidence: 99%
“…Metabolites in muscle play a crucial role in flavor and aroma characteristics, nutritional value, degradation, and biosynthesis of protein in fish. Metabolomics can detect variations in metabolic profiles of various low molecular weight metabolites, such as amino acids, lipids, and sugars (20,21). Gene expression can provide information on the expression activity of enzymes and functional proteins related to the proliferation and formation of myocytes (22).…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, such as China and Portugal, largemouth bass have been one of the most frequently farmed freshwater species for food, due to its rapid growth, flesh palatability, and ability to satisfy market demand [132,[203][204][205]. More than 700,000 tons of bass were produced in China in 2021 alone.…”
Section: Socio-economic Implications Of Bass Introductionsmentioning
confidence: 99%
“…More than 700,000 tons of bass were produced in China in 2021 alone. These have stimulated the procurement and production of both natural and artificial feeds to further increase flesh quality and optimize fish farming yields [132,203,204]. However, any unintentional spillover of individuals from artificially managed systems into natural habitats may extend the area of impact (and associated economic losses) far beyond the small areas of intentional introduction [6,200].…”
Section: Socio-economic Implications Of Bass Introductionsmentioning
confidence: 99%